Contractor Remedies for Employer Breach in Contemporary Saudi Construction Contracts: A Comparative Analysis from a Sharīʿah Perspective - Abdulrahman Mohammed Alzeer (MILRev: Metro Islamic Law Review, 2026)
Construction disputes arising from employer-caused delays, work suspensions, and delayed payments continue to pose significant challenges both globally and in Saudi Arabia. Existing scholarship has focused predominantly on contractor liability, paying comparatively little attention to contractors as injured parties who suffer material, operational, reputational, and psychological losses. This study examines the legal and Sharīʿah foundations governing contractor remedies under Saudi construction law by analysing the Saudi Civil Transactions Law (Royal Decree No. M/191), FIDIC contractual mechanisms, and the Islamic jurisprudential doctrine of ḍamān. Its principal contribution is the development of an analytical framework that classifies contractor losses into four categories: material, operational, reputational, and psychological. Employing a doctrinal, comparative, and normative harmonisation methodology, the study analyses statutory provisions, judicial decisions, FIDIC clauses, and classical Ḥanbalī legal sources. The findings demonstrate that employer breaches can result in substantial consequential losses and that the interaction between FIDIC remedial mechanisms and the maqāṣid al-Sharīʿah objectives of preserving wealth (ḥifẓ al-māl) and preventing harm (dafʿ al-ḍarar) provides a normative bridge between international construction practice and Islamic law. Although Articles 138–139 of the Saudi Civil Transactions Law expressly recognise compensation for moral and psychological harm, this represents a statutory development that extends beyond the classical Ḥanbalī conception of ḍamān. The study concludes that a harmonised framework integrating Sharīʿah principles, Saudi statutory law, and FIDIC mechanisms offers a balanced and coherent model for contractor remedies in contemporary construction disputes. By developing an integrated analytical framework and clarifying the relationship between classical Ḥanbalī doctrine, contemporary Saudi law, and FIDIC practice, this study makes a significant contribution to the literature on construction law and Islamic commercial jurisprudence.